Comparison of Moducare versus Wait-and-See approach for histologically proven Low-grade Cervical Intraepithelial Neoplasia (CIN1) (MODUCIN1 TRIAL) – Study protocol - Dimitrios Zouzoulas; Iliana Sofianou; Kimon Chatzistamatiou; Vasilis Theodoulidis; Grigoris Grimbizis; Dimitrios Tsolakidis (PLoS ONE, 2026)
Human Papillomavirus (HPV) is causally associated with cervical cancer and precancerous lesions (dysplasias) of the cervix. The treatment of choice for low-grade lesions is monitoring with no-treatment, because the majority of them will regress spontaneously. However, this wait-and-see approach can be assisted by nutritional supplements for immune support, like Moducare. The hypothesis of the trial is that Moducare can enhance the natural regression of CIN1. MODUCIN1 is a prospective, open-label, randomized trial where eligible patients will be randomized (1:1) to either the wait-and-see approach (control arm) or to the six months oral administration of Moducare capsules. The main inclusion criterion is newly histologically proven CIN1 and the main exclusion criterion is any previous cervical intraepithelial neoplasia with or without treatment or history of pelvic malignancy. The primary objective is to compare the regression rates of low-grade cervical intraepithelial neoplasia (CIN1) between the two groups: Wait-and-see approach and Moducare. The sample size is estimated at 182 eligible patients, while accrual is expected to last one year. The primary endpoint is expected to be reached after six months from last patient enrollment. The Trial Registration Number is NCT07379905.